Elevated serum thyrotropin levels and endothelial dysfunction in a prospective hemodialysis cohort. Issue 1 (6th July 2021) - You, Amy S.; Budoff, Matthew; Zeb, Irfan; Ahmadi, Naser; Novoa, Alejandra; Flores, Ferdinand; Hamal, Sajad; Kinninger, April; Dailing, Christopher; Nakata, Tracy; Kovesdy, Csaba P.; Nguyen, Danh V.; et al.
Abstract: Introduction: Thyroid dysfunction is a highly prevalent yet under‐recognized complication in hemodialysis patients. In the general population, hypothyroidism has been associated with endothelial dysfunction due to impaired vasodilator synthesis and activity. Little is known about the association of serum thyrotropin (TSH), the most sensitive and specific single biochemical metric of thyroid function, with endothelial function in hemodialysis patients. Methods: In a secondary analysis of 99 patients from the Anti‐inflammatory and anti‐oxidative nutrition in hypoalbuminemic dialysis patients (AIONID) trial, we examined measurements of serum TSH and endothelial function ascertained by fingertip digital thermal monitoring (DTM), a novel method used to measure micro‐vascular reactivity, collected within a 90‐day period. DTM was used to measure changes in fingertip temperature during and after an ischemic stimulus (blood pressure cuff occlusion) as an indicator of changes in blood flow, and two DTM indices were assessed, namely adjusted (a) Temperature Rebound (TR), defined as the maximum temperature rebound post‐cuff deflation, and adjusted (b) Area Under the Temperature Curve (TMP‐AUC), defined as area under the curve between the maximum and minimum temperatures. We examined the relationship between serum TSH with impaired TR (separately) and TMP‐AUC (both defined as less than the median level of observed values) using multivariable logistic regression. Findings: In unadjusted and case‐mix analyses, higher serum TSH levels (defined as the three highest quartiles) were associated with lower (worse) TR (ref: lowest TSH quartile): ORs (95% CI) 2.64 (1.01–6.88) and 2.85 (1.08–7.57), respectively. In unadjusted and case‐mix analyses, higher TSH levels were associated with lower (worse) TMP‐AUC: ORs (95% CI) 2.64 (1.01–6.88) and 2.79 (1.06–7.38), respectively. Discussion: In HD patients, higher serum TSH levels were associated with worse micro‐vascular reactivity measured by DTM. Further studies are needed to determine if thyroid hormone supplementation improves endothelial function in hemodialysis patients with lower levels of thyroid function.